Efficient response surface method for practical geotechnical reliability analysis. (September 2015) - Zhang, J.; Chen, H.Z.; Huang, H.W.; Luo, Z.
Abstract: Although numerical models have been widely used in the geotechnical profession, their applications for reliability analysis are still rather limited mainly because most geotechnical numerical programs lack the probabilistic function. In this study, an efficient response surface method is suggested for geotechnical reliability analysis using existing numerical programs. The developed approach can effectively avoid the occurrence of negative values for positive random parameters, and thus it solves the key limitation of the classical response surface method in geotechnical applications. To facilitate its application, a procedure is designed for automating reliability analysis with the commercially available program, FLAC3D. The developed method and procedure are demonstrated in detail using a slope example. The versatility of the suggested procedure is illustrated through the serviceability reliability analysis of a soft ground improved with deep mixing columns. For the reinforced ground studied in this paper, the reliability is mainly governed by the uncertainties in Young's moduli of the soil and reinforced columns. The suggested method can be conveniently used for reliability-based design of deep mixing columns.